Implementasi media muhadatsah dalam pembelajaran bahasa arab santri Pondok Pesantren Nurul Ilmi Bogor - Dhimas Fajri Putra Pratama; Nurul Latifatul Inayati (At Turots: Jurnal Pendidikan Islam, 2023)
This research is entitled "Implementation of Muhadatsah Media in Arabic language learning for students at Nurul Ilmi Islamic Boarding School, Bogor. The aim of this research is to describe the implementation of muhadatsah media for students at Nurul Ilmi Islamic Boarding School. This research method uses qualitative research by interviewing ustadz and students of the Nurul Ilmi Islamic boarding school in Bogor. The results of the interview on the implementation of muhadatsah media at the Nurul Ilmi Islamic boarding school where the students' mastery of the Arabic language has developed quite well with muhadatsah media, the boarding school carries out activities or this muhadatsah media to train the students' Arabic language or help the students understand Arabic. Santri must communicate in the official language. This type of qualitative research that focuses on interviews is descriptive using interviews.